Statistical energy analysis applied to structure-borne noise in computer equipment - Ooi, Tak Koon. (2008)
This project presents the analysis of structure-borne noise in computer tower structure by statistical energy using the AutoSEA software, and followed by experimental verification. Optimization of noise and vibration transmission by damping application and plate geometry change, and development of optimal design modification technique by statistical energy analysis have also been carried out following the analysis.